Stakeholder Perceptions of Religious Tourism and Local Development: Evidence from Lamego (Portugal) historic town - Rodrigues, Ana Paula (The international journal of religious tourism and pilgrimage, 2019)
The purpose of this study is to explore the views of different stakeholder groups (visitors, residents and local agents - heritage managers, tour operators, local authorities, Priests and head of the Church, directors of institutions linked to tourism) about the relationship between religion and tourism in a historic town setting. The main purpose is to examine the opinions/views/perceptions of different stakeholder groups about religious tourism and local development. A mixed methodological (quantitative and qualitative) approach was used in order to analyse the perceptions and opinions of three stakeholders groups. The opinions of visitors (120) and residents (150) were analysed using a quantitative methodology. Univariate and bivariate analysis were used as techniques of data analysis. In the study of the remaining stakeholder group (local agents) a qualitative research method (individual interviews) was used for data collection. In total, 19 in-depth interviews were conducted and content analysis was performed. The potential of this historic town for religious tourism was broadly supported by all the groups surveyed. Initiatives that take advantage of this potential to develop territories need intervention capacities that maintain a balance between political, economic and religious sensitivities. In this sense, agents and actors responsible for the development of tourism should work, in a coordinated and strategic manner on issues such as communication, networking, trust of the residents and their inclusion / involvement in all plans of action, benchmarking, and infrastructures. Specifically, it is important that stakeholders are encouraged to participate in tourism development processes at this location, especially with regard to religious tourism. This study highlights the importance of analysing the visions and perceptions of the various stakeholder groups in the whole process of tourism development in general and in the development of religious tourism in particular.